The Role of Cities in International Relations: The Third-generation of Multi-level Governance? - Szpak, Agnieszka; Gawłowski, Robert; Modrzyńska, Joanna (Cities series, 2022)
Concerns about the position and function of nation-states in the international arena have led to a growing interest in the role of cities in international relations. This timely book advances the argument that cities are becoming active and informal actors in international law-making, indicating the emergence of a ‘third generation’ of multi-level governance.